EVALUATION OF THE SUCCESSFUL APPLICATION OF MOVEAPS AT PT. PIXEL RESEARCH - Harfebi Fryonanda (JUTI: Jurnal Ilmiah Teknologi Informasi, 2022)
Evaluation of success in IS is an important aspect that must be done to develop information systems. Over time, the paradigm of evaluating the success of information systems continues to change according to the objectives, context, and impact of information technology. The information system evaluation models that can be used include the DeLone and McLean Information Systems Success Model (DM IS Model), Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology, and others. Each model has a different purpose, so the evaluator must choose the model that suits his needs. Moveaps application is an application developed by PT. Pixel Research. The Moveaps application is used to support every research project and online research needs. The evaluation of these systems adopts the DM IS Model. The model adopted in this study used all the variables in the DM IS Model and added intrinsic motivation. Thus, the variables become 8 variables consisting of 1) Information quality, 2) System quality, 3) Service quality, 4) Intrinsic motivation, 5) Perceived interaction, 6) Usage, 7) User satisfaction, and 8) Net impact. Previously identified variables, then a model of the relationship between variables was developed. The relationship between variables produces 16 hypotheses. This hypothesis is then compiled into several questions that are arranged in the form of a questionnaire. Questionnaires were distributed to 41 Moveaps Users. The results of 16 hypotheses found five hypotheses that have a positive effect, namely: information quality has a positive effect on service quality, system quality has a positive effect on information quality, system quality has a positive effect on service quality, user satisfaction has a positive effect on net benefits, and usage has a positive effect on benefits. Clean. While 11 hypotheses have no effect.